1996
DOI: 10.1021/jp960008o
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Bonding of C2H2 on Diamond C(111)−1×1:H:  Infrared Spectroscopy and Exciton Calculations

Abstract: The van der Waals interactions of acetylene with hydrogen-terminated diamond single crystal surfaces have been explored using infrared polarization spectroscopy at 83 K. By observing infrared spectra of the antisymmetric stretch of C 2 H 2 , the molecules are found to be adsorbed first on defect sites. This is followed by the adsorption on flat terraces that yields a single absorption at ν 0 ) 3225.6 cm -1 with a fwhm ) 5.4 cm -1 . The adsorbates lie nearly flat on the surface with a monolayer packing density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…[2][3][4][5][6][7]28,29,[46][47][48][49][50] The highly nonstatistical nature of the predissociation event is reflected in the 30-fold decrease 4 in lifetime for HF-*HF vs *HF-HF as well as the bimodal j distribution of the HF fragments. 29 Furthermore, since even ''fast'' vibrational predissociation in these complexes occurs on a time scale of many hundreds of thousands of monomer vibrational periods, these represent exceedingly ''rare'' intermolecular energy transfer events, i.e., with very low probability per oscillation of the monomer.…”
Section: B Vibrational Predissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7]28,29,[46][47][48][49][50] The highly nonstatistical nature of the predissociation event is reflected in the 30-fold decrease 4 in lifetime for HF-*HF vs *HF-HF as well as the bimodal j distribution of the HF fragments. 29 Furthermore, since even ''fast'' vibrational predissociation in these complexes occurs on a time scale of many hundreds of thousands of monomer vibrational periods, these represent exceedingly ''rare'' intermolecular energy transfer events, i.e., with very low probability per oscillation of the monomer.…”
Section: B Vibrational Predissociationmentioning
confidence: 99%
“…The tunneling and K dependence is even more pronounced in the v HF ϭ2 manifold, which has been rationalized in terms of a dynamical coupling with the other members of the v HF ϭ2 triad. Chang and Klemperer 6,7 have observed all four members of the v HF ϭ3 tetrad of HF-HF, a system which demonstrates the highest mode selectiv-a͒ ity observed to date; specifically, the predissociation lifetimes for states with all three quanta in the bound vs free HF stretch differ by 100-fold. Recently, Anderson et al 8 have observed all four intermolecular vibrations in the v HF ϭ1 manifold of HF-HF, accessed as combination bands built upon either the free or bound HF stretch.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, infrared ͑IR͒ spectroscopy was used to examine the vibrational dynamics of hydrogen, deuterium-covered diamond surfaces. 22,[25][26][27][28][29][30] From a peak width at the resonance frequency of 2120 cm Ϫ1 , a lifetime of 0.2 ps was found for C-D stretches on a D/C͑111͒ surface at room temperature. 22 A frequency of 2835.5 cm Ϫ1 at room temperature and small redshifts at high temperatures up to 1000 K were observed using IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen on diamond surfaces has received a great deal of attention recently because of its role in chemical vapor deposition of diamond thin films. The growth mechanism is substantially influenced by energy transfer between the vibrational modes on the surface and in the bulk. Many experiments have been carried out to probe the vibrational modes and the interactions between the adsorbates and surfaces on various surfaces. Because of the development of the sum-frequency generation (SFG) spectroscopy, the vibrational modes on the surface can be resolved in the frequency domain as well as the time domain. On hydrogen-covered H/C(111) diamond surface, the C−H stretching mode was measured to be 2835.5 cm -1 using Infrared (IR) spectroscopy .…”
Section: Introductionmentioning
confidence: 99%